Learning Cities and Urban Ecosystems. Digital Technologies fostering informal lifelong environmental education in cities and urban participation - Ingrassia, Marco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
Cities are crucial in environmental education. Urban contexts serve as immersive learning environments and outdoor classrooms facilitating direct contact with nature. In a socio-ecological perspective, cities can be seen as the object of education, if interpreted as complex urban ecosystems with non-linear relation between their biotic and abiotic components. Furthermore, citizens represent key targets of environmental education, in a wide spectrum from awareness to participatory capacity. Within the challenges of ecological transition, transformation of urban lifestyles together with socio-economic and territorial models is necessary, as cities represent the main habitat of human population and the main cultural, political and economic centers. The UNESCO Learning Cities Network underscores the importance of cities in promoting lifelong and inclusive learning, fostering informal education models to reach a broader demographic, including adults excluded from formal and non-formal curricula. This challenge can be addressed through public and community strategies—such as events, public space design, activities in community spaces—and extensive use of digital technologies. They can support education through increased immersiveness, simulation, integration of informative layers and interaction, and accessibility. Furthermore, these tools are radically changing urban experience and management: IoT and digital interfaces provide information, change perceptions, and enable immersive inhabitation models, while data collection, AI, and 3D interfaces allow for complex, participatory management of urban spaces, economies, and territories. This contribution explores the role of digital technologies in enhancing informal lifelong environmental education in cities. By analyzing literature and case studies, it highlights emerging theoretical approaches and design solutions, and presents an interpretative framework to advance understanding and inform policies for urban environmental education. This framework is based on: (i) the five fundamental environmental education objectives (awareness, knowledge, attitudes, skills, participation) identified by UNESCO and UNEP; (ii) the four capacities of digital technologies for education (immersion, simulation, integration of informative layers and interaction, accessibility); and (iii) three types of digital technologies (augmented reality, video mapping for digital art, digital participatory platforms). The results reveal innovative methodologies and the need for further integration within policies and curricula.